A mixed formulation for the stress analysis of curved pipes with tangent terminations under in-plane forces - Madureira, Luisa R.
Curved pipes connected to tangent terminations play an important role in process equipment design where there is fluid transport. They allow change in flow direction and simultaneously contribute to increase flexibility of the whole structure. The stress analysis of curved pipes (or pipe elbows) is an essential step in the project of piping systems. The method of hybrid formulation of the shell parameters (internal forces and displacements), is an alternative to the irreducible formulation, this last dealing with a totally assumed displacement field for the unknowns. The main advantage has incidence in the use of lower order formulations in the differential equations to set-up the solution compared with the irreducible formulation. The hybrid solution here proposed is based on a semi-analytic formulation, where the definition of the shell forces and displacements combines analytic and trigonometric functions. Tests for most usual loading cases are analysed and results for stress distribution are discussed.